The Morphology and Corresponding Rheological Properties of Phase-Separating Polymer Blends Subject to a Simple Shear Flow - Luo, Kaifu; Yang, Yuliang (Macromolecular theory and simulations, 2002)
The chain‐stretching effect on the morphology and the corresponding rheological properties are analyzed theoretically. In order to confirm the theoretical analysis, the simulations based on the time‐dependent Ginzburg‐Landau (TDGL) equation with the free energy functional contains the information of chain conformation have been performed in q‐space by means of the semi‐implicit Fourier spectral method. This method is more efficient and accurate, and moreover, the periodic boundary condition used in r‐space cell dynamics scheme (CDS) can be released. The simulation results agree with the theoretical analysis quite well and show that the chain‐stretching effect decreases with the increase of shear strain. For the critical system with a longer terminal Rouse relaxation time, two peaks are observed in the transient shear viscosity. It is also found that, when the shear strain is small, the chain‐stretching effect on the morphology and the corresponding rheological properties are enhanced when the terminal Rouse relaxation time is longer.